2021
DOI: 10.21608/ajnsa.2021.26593.1360
|View full text |Cite
|
Sign up to set email alerts
|

Grafting Copolymerization of (Sodium Alginate/ Acrylic Acid/ MethacrylicAcid) by Gamma Radiation: Preparation and Characterization

Abstract: Grafted copolymer (sodiumalginate (Na. Alg)-acrylic acid (AcA)methacrylic acid (MAcA)) was prepared by the gamma irradiation-induced copolymerization in the presence of N, N-methylene bis-acrylamide (MBA) as aco monomer crosslinker. The functionality, morphology and thermal stability of the prepared copolymer have been examined using FTIR spectroscopy, SEM, and TGA-DTA, respectively. The prepared material shows a smooth surface and relatively homogeneous appearance which reveals incompatibility between the mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In other words, we can consider that, in terms of the glass transition temperature, the graft copolymers showed better thermal stability than the homopolymer (pAMD). Other reports also revealed that natural polysaccharides grafted with vinyl monomer by means of ionizing radiation had good thermal stability in the field of practical applicability [ 47 , 70 , 71 ]. Moreover, da Silva et al [ 33 ] clearly proved that grafting of pAMD chains onto the polysaccharides enhances their thermal stability.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, we can consider that, in terms of the glass transition temperature, the graft copolymers showed better thermal stability than the homopolymer (pAMD). Other reports also revealed that natural polysaccharides grafted with vinyl monomer by means of ionizing radiation had good thermal stability in the field of practical applicability [ 47 , 70 , 71 ]. Moreover, da Silva et al [ 33 ] clearly proved that grafting of pAMD chains onto the polysaccharides enhances their thermal stability.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained results showed that employing 20% AcA, 10% MAcA, and 0.4 weight percent NaAlg at an irradiation dose of 15 KGy with the addition of 0.03% MBA as a crosslinker are the ideal circumstances for producing a good grafted co polymer. All ingredients are combined in glass tubes and given a 25 kGy dose of 60Co gamma radiation [9][10].…”
Section: Preparation Of Sodium Alginate Poly(acrylic Acid-methacrylic...mentioning
confidence: 99%
“…Alginate salt is a natural polymer that has been used to mix with synthetic polymers like acrylic acid and its derivatives [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that cation binding sites in fulvic acid are mainly carboxylic groups [ 35 , 36 , 37 ], and the chemical modification of BFA to improve its carboxyl content can effectively solve the problem. Among the various modifiers, AA is chosen because it is easy to polymerize and able to provide the necessary carboxylic groups [ 38 , 39 , 40 , 41 ]. Potassium peroxydisulfate is a quite effective initiator in grafting copolymerization [ 42 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%